2023
DOI: 10.1177/24741264231156094
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Virtual Vitreoretinal Surgery Fellowship Interview and Match Experience

Abstract: Purpose: To evaluate applicants’ and programs’ experiences during the 2019 and 2020 fellowship application seasons. Methods: An anonymous survey of vitreoretinal surgery fellowship program directors (PDs) (n = 21) and applicants from the 2019 traditional (n = 24) and 2020 virtual (n = 17) match cycles (before and during COVID-19 pandemic, respectively) was conducted. The questions assessed demographics, interview experiences, and overall interview costs. Statistical significance was determined using unpaired a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…More specifically, multiple surveys have shown that fellowship applicants are interested in hybridized approaches to interviewing in order to better understand program culture (17,18). Concerns about communicability and security, which we found in the Empathize and Define phases, are echoed in another survey of vitreoretinal surgery fellowship applicants who expressed similar concerns (19). Another survey, among hand surgery fellowship applicants, showed how fellow applicants prioritize time with current fellows, another key finding of our investigation (20).…”
Section: Discussionmentioning
confidence: 76%
“…More specifically, multiple surveys have shown that fellowship applicants are interested in hybridized approaches to interviewing in order to better understand program culture (17,18). Concerns about communicability and security, which we found in the Empathize and Define phases, are echoed in another survey of vitreoretinal surgery fellowship applicants who expressed similar concerns (19). Another survey, among hand surgery fellowship applicants, showed how fellow applicants prioritize time with current fellows, another key finding of our investigation (20).…”
Section: Discussionmentioning
confidence: 76%
“… 7 Another study of retina fellowship applicants by Gill and colleagues compared in-person and virtual experiences; however, this comparison was across years, with in-person interviews prior to the AUPO mandate and virtual after. 2 This year-to-year comparison may leave room for confounding factors such as recall bias and inter-year variability in competitiveness of the match (based on variable number of applicants and positions) that may affect the level of anxiety or number of applications and interviews completed, as well as annual inflation and variation in costs between years. Importantly, interviewing participants who experienced both in-person and virtual interviews in close juxtaposition within the same application cycle allowed the opportunity to ask which type of interview format they preferred or would select if given the choice.…”
Section: Discussionmentioning
confidence: 99%
“…Across various medical specialties, there has been robust debate between those favoring the return to in-person interviews and those wishing to continue the interview process virtually. While some cite decreased cost and increased flexibility in favor of virtual interviews, 1 2 3 4 there also remain concerns that applicants cannot experience intangible aspects of the program and that there is an increased opportunity for misrepresentation, whether intentional or not, on the part of the program, applicants, or both. 2 5 6 Retina fellowship programs encompass one subset of fellowship applicants that have been surveyed.…”
mentioning
confidence: 99%
See 2 more Smart Citations